2020
DOI: 10.1007/s13224-020-01366-w
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression and Behavioural Changes in Junior Doctors and Medical Students Associated with the Coronavirus Pandemic: A Cross-Sectional Survey

Abstract: Introduction Medical students are known to have high levels of depression, anxiety and stress from the high-pressure environments that they study and train in. The coronavirus pandemic presents source of stress and anxiety to large populations in general, and to healthcare professionals in particular. This study was undertaken to assess the psychological effects of this pandemic on the mental health of medical students and trainees. Materials and Methods An online quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 9 publications
6
75
3
2
Order By: Relevance
“…Details and outcomes related to the mental health of included articles are provided in Table 1 . 3 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 All 22 cross-sectional studies were carried out in the Indian population, with age ranging from 12 to 82 years, and the majority of study participants were above 18 years. These 22 studies enrolled a total of 9947 participants, including 5542 (55.7%) males and 4405 (44.3%) females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details and outcomes related to the mental health of included articles are provided in Table 1 . 3 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 All 22 cross-sectional studies were carried out in the Indian population, with age ranging from 12 to 82 years, and the majority of study participants were above 18 years. These 22 studies enrolled a total of 9947 participants, including 5542 (55.7%) males and 4405 (44.3%) females.…”
Section: Resultsmentioning
confidence: 99%
“… Gupta et al 3 July- 2020 Across India Cross-sectional 1124 Health care workers (HCWs) 718 (63.88%) Online survey HADS Scale HADS score 8 & above Depression & anxiety Khanna et al 25 June- 2020 Across India Cross-sectional 2355 Ophthalmologists Mean age: (42.5 ± 12.05), Range: 25-82 1332 (56.56%) Online survey PHQ-9 - Depression Mishra et al 26 June- 2020 Across India Cross-sectional 716 Ophthalmology trainees Mean age: (29.1 ± 3.14), Range: 23-45 275 (38.41%) Online survey self-reported questionnaire - Stress Muruganandam et al 27 June- 2020 South India Cross-sectional 132 patients diagnosed with severe mental illness [SMI] and their primary caregivers Mean age: (33.9 ± 10.9), Range: 21-52 63 (47.73%) Telephonic survey 23- item questionnaire - Impaired sleep, suicidal ideas and taking substances or illegal drugs. Pandey et al 28 September-2020 Uttar-Pradesh Cross-sectional 83 Final year medical students and Obstetrics and Gynaecology trainees 80 (96.4%) wer...…”
Section: Resultsmentioning
confidence: 99%
“…Similarly doctors, nurses and other health care professionals were misbehaved and attacked by the public (A. Pandey, 2020; V. Pandey, 2020).…”
Section: Future Directionsmentioning
confidence: 99%
“…[53][54][55] Imposition of unfamiliar public health measures including social distancing and lockdown, social fear related to COVID-19, closures of universities, fear of being infected by the SARS-CoV-2, anxiety for their removal from clinical practice, worry about older relatives and the abrupt swift to a new reality have negative impact on the psychological well-being of medical students. 56 While individual studies from Turkey, India and Iran and European countries like Malta [57][58][59][60][61] showed that the prevalence of depression and anxiety in medical students was significantly high, a recent systematic review and meta-analysis indicated that the prevalence of anxiety in medical students is similar to that prior to the pandemic. 49 Interestingly, a cross-sectional study showed that medical students' burnout syndrome, depression, anxiety and somatic symptoms rates decreased during online learning.…”
Section: Mental Healthmentioning
confidence: 99%